(untitled) (Medico Legal Update, 2021)
The present study was conducted to identify the differences in body esteem and sexual assertiveness between male and female college students. A total of 288 students (156 males and 132 females) from a university in Chungnam, South Korea, participated in this study. A self-administered questionnaire survey with the study participants was conducted from December 1 to 14, 2018. The data obtained were analyzed using descriptive statistics, c2 test, analysis of covariance, t test, one-way analysis of variance (Scheffé test for post hoc analysis), and linear regression with the IBM SPSS 20.0 program. Body esteem among the male students was higher than that among the female students, whereas sexual assertiveness among the female students was higher than that among the male students. Body esteem differed according to body image perception in the male students and according to body image perception as well as the number of romantic relationships in the female students. Sexual assertiveness differed according to grade level and body image perception in the male students only. In all the study participants, the higher the body esteem, the higher the sexual assertiveness. These results indicate that (1) interventions that increase the body esteem of female students should be provided and (2) interventions that increase sexual assertiveness should factor in body esteem. Additionally, developmental interventions for body esteem and sexual assertiveness should consider body image perception.